Where does the moral groundwork come from in today’s society? - ks. Piotr Mazurkiewicz (Chrześcijaństwo-Świat-Polityka)
The article shows sociological and moral dilemmas of modern liberal democracies resulting from the fact that liberalism has become radically secular. The author raises the issue of the origin of this state of affairs, as well as of paradoxes that arise while these societies search for justification of moral positions.